The Personality Pedagogical Culture of a Teacher: Systematic and Synergetic Approaches to the Analysis - Yurii Plyska (Pedagogical Discourse, 2017)
In the article, according to the analysis of the typology, the author states the most appropriate basic principles for the classification of system objects. Static’s is a characteristic of a system that states the inalterability of its condition during certain time. According to the fact that personal pedagogical culture of a teacher is constantly being changed, it is a dynamic system. The determined system objects enable defining their condition using certain criteria and indicators at any period of time. Instead, probabilistic objects are only prognostically defined. The closed system is characterized by absence of external influences that change the nature and content of its elements. The open system is characterized by a constant exchange of its content both internally and externally. The above analysis of the typology and its projection on the study perspective makes it possible to conclude that the teacher personal pedagogical culture is a dynamic, probabilistic open system. Moreover, this conclusion is important in terms of analysis of this phenomenon in the Ukrainian and global realities within the systematic and synergistic research approaches.Thus, in the article the place and role of systematic and synergistic approaches in the process of analyzing personal pedagogical culture of teachers are determined. What is more, the systematic characteristics of personal pedagogical culture as a scientific concept are found; interrelation of systematic principles and their impact on the analysis of personal pedagogical culture of teachers are explained. It has been concluded that personal pedagogical culture of a teacher is a dynamic, probabilistic open system.The author has determined the synergistic principles of personal pedagogical culture. Moreover, it is stated that the prospect of further research is to study the field of cultural and axiological foundations of this phenomenon.Key words: system, synergetics, personality, pedagogical culture.